2020
DOI: 10.1038/s41598-020-59120-1
|View full text |Cite|
|
Sign up to set email alerts
|

The endocannabinoid hydrolase FAAH is an allosteric enzyme

Abstract: Fatty acid amide hydrolase (FAAH) is a membrane-bound homodimeric enzyme that in vivo controls content and biological activity of N-arachidonoylethanolamine (AEA) and other relevant bioactive lipids termed endocannabinoids. Parallel orientation of FAAH monomers likely allows both subunits to simultaneously recruit and cleave substrates. Here, we show full inhibition of human and rat FAAH by means of enzyme inhibitors used at a homodimer:inhibitor stoichiometric ratio of 1:1, implying that occupation of only on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 48 publications
1
16
0
Order By: Relevance
“…For MAGL, it was shown that its irreversible inhibitors, through prolonged inactivation of this enzyme, may cause physical dependence, CB1 desensitization, and impaired eCB-dependent synaptic plasticity [68]. Moreover, MAGL and FAAH form homodimers [66,69]. Recently, FAAH dimers have been proven to be dependent on the signaling between their subunits and its allosteric regulation.…”
Section: Molecular Mechanisms Of the Main Proteins Of Ecs-implicationmentioning
confidence: 99%
See 1 more Smart Citation
“…For MAGL, it was shown that its irreversible inhibitors, through prolonged inactivation of this enzyme, may cause physical dependence, CB1 desensitization, and impaired eCB-dependent synaptic plasticity [68]. Moreover, MAGL and FAAH form homodimers [66,69]. Recently, FAAH dimers have been proven to be dependent on the signaling between their subunits and its allosteric regulation.…”
Section: Molecular Mechanisms Of the Main Proteins Of Ecs-implicationmentioning
confidence: 99%
“…Recently, FAAH dimers have been proven to be dependent on the signaling between their subunits and its allosteric regulation. Thus, it may be possible to design allosteric modulators of FAAH [69]. TRPV1 is a non-selective channel.…”
Section: Molecular Mechanisms Of the Main Proteins Of Ecs-implicationmentioning
confidence: 99%
“…These methods are optimized for quantitating the rate of (i) MAG biosynthesis in intestinal epithelium and lung tissue via DGL, (ii) MAG degradation in intestinal epithelium and lung tissue via MGL, (iii) MAG degradation via ABHD6 in lung tissue, and (iv) FAE degradation in intestinal epithelium and lung tissue via FAAH. Notably, we provide novel methods that do not require radioactive substrates to assess activity of FAAH in mouse mucosal tissues as described elsewhere (Fu et al, 2007;Dainese et al, 2020), and expand and optimize to lung tissue application of our previously-reported UPLC-MS/MS-based assays of DGL and MGL activity in intestinal epithelium (Batugedara et al, 2018;Argueta et al, 2019). Furthermore, the UPLC-MS/MS methods described here are ideal for detecting discrete changes in the activity of enzymes that metabolize eCBs and related lipids given that these enzymatic reactions involve hydrolysis of substrates leading to detectable changes in substrate mass.…”
Section: Discussionmentioning
confidence: 99%
“…These methods are optimized for quantitation of the rate of metabolism of eCBs by DGL, MGL, ABHD6, and FAAH. Moreover, novel methods are described for measuring FAAH activity that does not require use of radioactive compounds as substrates (Fu et al, 2007;Dainese et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, Maccarrone and co‐workers provided evidence for the existence of an allosteric regulation of FAAH, involving a functional cross‐talk between its monomers. This evidence offers the potential opportunity to elegantly fine‐tune FAAH activity by targeting regulatory sites [137] …”
Section: Faah Inhibitors In Msmentioning
confidence: 99%